Digital Financial Inclusion and Sustainable MSME Resilience in Indonesia’s Asta Cita Agenda: A Structured Narrative Review (Jurnal Lemhannas RI, 2025)
Purpose: This review examines how digital financial inclusion strengthens the resilience of micro, small and medium enterprises (MSMEs) and its relevance to Indonesia’s Asta Cita development agenda and economic resilience. It focuses on how access to digital financial services develops into organisational capabilities that help MSMEs withstand disruption, adapt to change and sustain long-term viability.Design/methodology/approach: The study uses a structured narrative review of peer-reviewed literature published between 2016 and 2025 from Scopus, Web of Science, ScienceDirect, Emerald Insight and SpringerLink, supported by selected Google Scholar studies and Indonesian policy documents. The review synthesises evidence on mechanisms, capabilities, resilience outcomes and boundary conditions.Findings: The review identifies four mechanisms: liquidity access, transactional visibility, managerial information and ecosystem connectivity. These mechanisms foster absorptive, adaptive and transformative resilience when MSMEs develop sensing, seizing and reconfiguring capabilities. Their effectiveness depends on digital literacy, affordability, trust, infrastructure, institutional support, consumer protection and regulatory readiness.Originality/value: The review develops a capability-conversion framework explaining why similar digital financial technologies produce different resilience outcomes. It links firm-level capability development with Asta Cita priorities and demonstrates its relevance to inclusive economic resilience and sustainable national development.
Keywords: Asta Cita; Digital Financial Inclusion; Dynamic Capabilities; Economic Resilience; MSME Resilience